Vancomycin presoaking of hamstring grafts removes the risk of infection in primary anterior cruciate ligament reconstruction. Issue 12 (31st December 2018) - Figueroa, Francisco; Figueroa, David; Calvo, Rafael; Vaisman, Alex; López, Mario; Goñi, Ignacio
Background: Several strategies have been studied to decrease the rate of infection after hamstring autograft anterior cruciate ligament (ACL) reconstruction. Our group started presoaking grafts with Vancomycin in November 2015 to decrease this risk. Purpose: The objective of the study is to compare the success of this protocol against the immediate previous period in which we did not use the protocol. Study design: Retrospective cohort. Level III. Methods: Consecutive periods were studied: April 2013-October 2015 (pre Vancomycin protocol) and November 2015- May 2018 (Vancomycin protocol). All patients that underwent a hamstring autograft primary ACL reconstruction during the periods studied were included. The final outcome was the presence of postoperative septic arthritis in both groups. Diagnosis of septic arthritis was made using the clinical picture plus cytological analysis of a joint aspiration (cell count > 50.000/uL + > 90% neutrophils) Statistical analysis was made using the Fisher's exact test. Significance was set in p < 0.05. Results: 490 patients were included in the study, 230 in the pre Vancomycin protocol an 260 in the Vancomycin protocol. 4 postoperative septic arthritis were noted in the pre Vancomycin protocol (1.7%) while no septic arthritis was noted in the post Vancomycin protocol patients during the period studied. (p < 0.05) The 4 postoperative infections were presented at an average 21.7 days (range 16-25). Staphylococcus epidermidis was isolated in 2 of the cases, and in the other 2 no organism was isolated. Conclusion: Vancomycin presoaking of hamstring autografts in primary ACL reconstruction eliminated the risk of postoperative septic arthritis during the studied period compared to the immediate previous period, where no Vancomycin presoaking was used.